Deterministic Writing and Control of the Dark Exciton Spin Using Single Short Optical Pulses - I. Schwartz; E. R. Schmidgall; L. Gantz; D. Cogan; E. Bordo; Y. Don; M. Zielinski; D. Gershoni (Physical Review X, 2015)
We demonstrate that the quantum dot-confined dark exciton forms a long-lived integer spin solid-state qubit that can be deterministically on-demand initiated in a pure state by one optical pulse. Moreover, we show that this qubit can be fully controlled using short optical pulses, which are several orders of magnitude shorter than the life and coherence times of the qubit. Our demonstrations do not require an externally applied magnetic field, and they establish that the quantum dot-confined dark exciton forms an excellent solid-state matter qubit with some advantages over the half-integer spin qubits, such as the confined electron and hole, separately. Since quantum dots are semiconductor nanostructures that allow integration of electronic and photonic components, the dark exciton may have important implications for implementations of quantum technologies consisting of semiconductor qubits.